Meesterlijke handen: Instrumentenbouw en vakmanschap vandaag - Maes, Mirte; De Paepe, Timothy 1981-; Museum Vleeshuis | Klank van de Stad (Antwerp, Belgium) (Antwerp BAI, 2024)
'Museum Vleeshuis' not only preserves musical instruments, but also the stories and craftsmanship of the people behind them. In this Cahier, we turn the spotlight on today's instrument makers, whose masterful hands bring sounds to life. Who are these craftsmen? What does their working day look like? What drives them, and what dreams do they cherish? This booklet offers an insight into the daily lives of Bram De Man, Daniël Vernooij, Justin Glaie, Koen Fonteyne, Maarten De Keukeleire, Rebekka De Backer, Sandra Van der Jeught, Stephan Van Meirhaeghe, Stijn Kenens, Tim Duerinck & Toon Lauwers, full of skill, passion and dedication.
Keywords: 21st Century (2001-2100); Musical instrument makers; Organology; Belgium